The DUF1669 domain of FAM83H is required for its localization to nuclear speckles - Takahisa Kuga; Minami Saraya; Sora Higuchi; Shun Yoshida; Shino Murataka; Yuri Fujiwara; Yudai Tomita; Sayo Hayama; Yuichiro Kaibori; Nobuyuki Yamagishi (Scientific Reports)
Abstract Autosomal-dominant hypocalcified amelogenesis imperfecta (ADHCAI) is caused by mutations in the FAM83H gene. Mutated FAM83H genes encode truncated FAM83H proteins with amino acid lengths between amino acids 1–286 and 1–693, in contrast to wild-type FAM83H (1–1179). Deletion of the C-terminus of FAM83H results in its subcellular translocation from the cytoplasmic compartment to the nuclear speckles, where splicing factors accumulate. However, the amino acid region of FAM83H required for nuclear speckle localization has not yet been determined, and whether all FAM83H-truncated proteins associated with ADHCAI localize to nuclear speckles remains unknown. Here, we examined the subcellular localization of FAM83H mutant proteins with truncations or deletions at various amino acid positions. Deletions within residues 1–300, which corresponds to the DUF1669 domain (17–281), attenuated or abolished the nuclear speckle localization of FAM83H. Meanwhile, some ADHCAI-related FAM83H-truncated proteins did not localize to nuclear speckles, despite the presence of the DUF1669 domain. These results suggest that the DUF1669 domain is required, but not sufficient, for nuclear speckle localization of FAM83H, demonstrating that nuclear speckle localization is not a common feature among FAM83H-truncated proteins related to ADHCAI.